Fist record of Bochianites neocomiensis (D’Orbigny) in Argentina and associated calcareous nannofossils bioevents: strengthening the early Valanginian correlation of the Andes with the Mediterranean Tethys - Marin, Luciana Sabina (2022)
Bochianites neocomiensis, a long-ranging and widespread ammonoid species from the Tithonian to the early Barremian, is recorded for the first time in the Neuquén Basin, in the upper levels of the Vaca Muerta Formation at Cañada de Leiva, southern Andes of Mendoza, Argentina. There a 40 m section encompassing the Lissonia riveroi and Olcostephanus atherstoni zones was bed-by-bed sampled for ammonoids and calcareous nannofossils. A total of 125 specimens of B. neocomiensis, either flattened or preserved as imprints, were retrieved from two levels of dark-brownish mudstones near the base of the section. The same beds yielded L. riveroi, an endemic Andean ammonite restricted to the lower Valanginian (Aguirre-Urreta and Rawson 1999). The occurrence of Eiffellithus windii from the base of the studied section allowed the recognition of the CC3-B nannofossil subzone (Applegate and Bergen 1988), which together with the co-ocurrence of B. neocomiensis and L. riveroi, enable the correlation of those levels with the Neocomites neocomiensiformis ammonite zone from the Western Mediterranean Province of the Tethyan Realm (Reboulet et al., 2014). In addition, in the last level yielding O. atherstoni the FO of Eiffellithus striatus was identified, a calcareous nannofossil bioevent that indicates the base of the CC4-A nannofossil subzone and correlates with the base of the Western Mediterranean Saynoceras verrucosum ammonite zone. This finding reinforces the correlation of the O. atherstoni subzone with the Karakaschiceras inostranzewi ammonoid zone. The mix of a cosmopolitan ammonoid like B. neocomiensis in association with endemic Andean ammonites and their calibration with new calcareous nannofossils data helps refining the long-distance correlation between the west-central Argentina biozonal scheme and the Ammonite standard zonation for the Valanginian.